The Impact of Fiscal Policy on the Manufacturing Industry of Uganda Case Study of Coca Cola Beverages Uganda - Ian Emmanuel Katwere (Uganda Christian University, 2024)
Although the government has implemented a number of policies aimed at improving Uganda’s economic growth through the contribution of the manufacturing industry and the utilisation of the sector’s capacity, fiscal policy has increasingly become a source of concern in terms of its role in the performance of Ugandan manufacturing industries. The purpose of this study was to determine the impact of fiscal policy on Uganda’s industrial output. Empirical evidence from both developed and developing economies has clearly demonstrated that fiscal policy, when properly handled, has the potential to influence the entire economy. The research adopted a quantitative and qualitative cross-sectional survey design. The idea and reason behind the adoption of a cross-sectional survey design are that it involves the measurement variables by asking people questions and then examining relationships among the variables at one point in time. Regarding this, the research design was considered appropriate as it would give an opportunity to make an intensive analysis of specific details over the data collected. Besides, the design intended to collect data without manipulating the research variables or the respondents themselves in order to get the genuine perception of the respondents. This led to the following conclusion in the research, government revenue has an influence on the returns on investment in an industry as well as an influence on the return on equity, on the return on sales, giving that government spending can influence inflation which affects the overall performance of an industry, Government revenue was found to be a big influence on the performance of industries in Uganda. Return on equity, return on sales, return on investment, return on net profit margin, the asset ratio, government income tax rate, government policy that influences performance of our company, and government policy on the rate of lending affects an Industry performance. Taxation as a fiscal policy tool affects both the efficacy and efficiency of Uganda’s manufacturing industry. Uganda’s fiscal policy on taxes has a considerable impact on the manufacturing sector’s output. As a result, the government can collect revenue through taxation and spend money, impacting the activities of manufacturing companies and other economic activities. This has led me to the conclusion that fiscal policy on taxation is highly important and must be carefully managed if industries are to actually remain competitive and viable.
Undergraduate Dissertation